Psychopathic Personality Traits Scale - Revised (PPTS-R): empirical investigation of construct validity and dimensionality in a forensic and non-forensic sample - Boduszek, Daniel (Deviant behavior, 2022)
The objective of the current study was to develop a revised version of the Psychopathic Personality Traits Scale (PPTS-R) with an increased number of indicators to more reliably capture the four dimensions of the Psychopathic Personality Traits Model (PPTM). Dimensionality, construct validity, and reliability of the PPTS-R was examined among general (N = 1989) and prison (N = 638) population. Three competing models of the PPTS-R were specified and tested using Mplus with MLR estimation. The current research provides evidence that the 28-item PPTS-R using 5-point Likert scale is best captured by four factors, including affective responsiveness, cognitive responsiveness, interpersonal manipulation, and egocentricity and can be effectively used in forensic and general population. Additionally, the PPTS-R will allow, for the first time, for meaningful comparisons between forensic and non-forensic populations with regards to the prevalence of psychopathic traits.